Effect of blast-induced fragment conditioning on impact breakage strength. (June 2014) - Parra, H.; Onederra, I.; Michaux, S.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper presents the results of controlled blasting experiments and blast modelling carried out to understand and quantify the effect of blasting on the creation of fractures inside fragments referred to as conditioning. Fragment conditioning is studied through the use of indirect and direct measurement techniques on samples collected from different zones around an explosive charge. Modelling is used to map different levels of conditioning throughout the blasted samples and explore the impact of boundary conditions on the spatial distribution of conditioning levels. Combined statistical analysis of repeatable tests showed that the measured impact breakage ranking parameter (A*b) increased by 20 and 33% within the low and intermediate conditioning zones respectively. This translates into a statistically significant strength reduction of the material. These results in conjunction with other documented experience suggest that blast-induced conditioning can have a positive impact on comminution performance and thus energy consumption. Results from this work provide the basis for a methodology to better define post-blast breakage strength inputs into comminution performance models; as well as a preliminary approach to scale up the extent and degree of conditioning by blasting. Further work is required to evaluate the ability to control the degree of conditioning through the application of improvements in designs and novel blasting technology